Survey on Environmental Care among UiTM Campus Tapah Student on Solid Waste Management using Mean Score and - Husna Jamian, Nural; Zulkipli, Faridah; Zulaikha Zulkifli, Ilya; Mohd Nopiah, Zulkifli (International Journal of Engineering and Technology, 2018)
The study is focusing on the environmental care components in solid waste management among students at UiTM Campus Tapah. This study is conducted through a questionnaire and involved a total of 354 students. The environment care components are consisting of knowledge, practice, attitude, perception and awareness. Statistical analysis of mean score and t-test are conducted in order to analyze the data collected. The results of the survey are highlighted that majority of the UiTM Tapah students had high knowledge level towards environmental care; and had very good practice in environment cleanliness; had a moderate concern on attitude, and the majority of the students had moderate perception in term of understanding and practicing solid waste separation and finally majority of students know their personal accountability towards environment care based on awareness component. As a conclusion, environmental care among students shows positive responses in Awareness, Practice, Attitude, Knowledge and Perception towards sustainable solid waste management in future.Â Â